2023
DOI: 10.3389/fpls.2023.1182266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strong wind on laminas and petioles of Farfugium japonicum (L.) Kitam. var. japonicum (Asteraceae)

Abstract: Farfugium japonicum (L.) Kitam. var. japonicum grows mainly in the coastal areas of Japan. Meteorological recording data from natural habitats were used to investigate the factors associated with the laminas and petioles of radical leaves of F. japonicum var. japonicum to avoid or resist higher wind stress. Our morphological and mechanical results indicated that petiole length and petiole cross-sectional area had a weak correlation with wind speed and breaking strength, and the petiole second area moment of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…var. japonicum (Asteraceae) has a decreased lamina size to reduce the movement of the petiole so that the petiole does not break against strong winds in coastal areas 5 . Sudden flooding and rising water levels after heavy rainfall, are also environmental stressors that affect plants that grow alongside rivers 6 .…”
Section: Introductionmentioning
confidence: 99%
“…var. japonicum (Asteraceae) has a decreased lamina size to reduce the movement of the petiole so that the petiole does not break against strong winds in coastal areas 5 . Sudden flooding and rising water levels after heavy rainfall, are also environmental stressors that affect plants that grow alongside rivers 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the first example of such responses is the reduction in plant height that usually occurs in plants exposed to wind or other MIS (Biddington, 1986). In this context, it has been shown that trees exposed to wind are shorter and more pointed, but have lower overall stiffness, although their mechanical properties are less affected by their morphology (Paul-Victor and Rowe, 2011;Shiba et al, 2023). In contrast, wheat plants are stronger and less flexible, but do not show a significant change in stem height under the influence of wind sway (Crook and Ennos, 1996).…”
mentioning
confidence: 99%